Novel Modulator for Endothelial Adhesion Molecules: Adipocyte-Derived Plasma Protein Adiponectin - Ouchi, Noriyuki; Kihara, Shinji; Arita, Yukio; Maeda, Kazuhisa; Kuriyama, Hiroshi; Okamoto, Yoshihisa; Hotta, Kikuko; Nishida, Makoto; Takahashi, Masahiko; Nakamura, Tadashi; Yamashita, Shizuya; Funahashi, Tohru; et al. (Circulation (New York, N.Y.), 1999)
Background —Among the many adipocyte-derived endocrine factors, we recently found an adipocyte-specific secretory protein, adiponectin, which was decreased in obesity. Although obesity is associated with increased cardiovascular mortality and morbidity, the molecular basis for the link between obesity and vascular disease has not been fully clarified. The present study investigated whether adiponectin could modulate endothelial function and relate to coronary disease. Methods and Results —For the in vitro study, human aortic endothelial cells (HAECs) were preincubated for 18 hours with the indicated amount of adiponectin, then exposed to tumor necrosis factor-α (TNF-α) (10 U/mL) or vehicle for the times indicated. The adhesion of human monocytic cell line THP-1 cells to HAECs was determined by adhesion assay. The surface expression of vascular cell adhesion molecule-1 (VCAM-1), endothelial-leukocyte adhesion molecule-1 (E-selectin), and intracellular adhesion molecule-1 (ICAM-1) was measured by cell ELISA. Physiological concentrations of adiponectin dose-dependently inhibited TNF-α–induced THP-1 adhesion and expression of VCAM-1, E-selectin, and ICAM-1 on HAECs. For the in vivo study, the concentrations of adiponectin in human plasma were determined by a sandwich ELISA system that we recently developed. Plasma adiponectin concentrations were significantly lower in patients with coronary artery disease than those in age- and body mass index–adjusted control subjects. Conclusions —These observations suggest that adiponectin modulates endothelial inflammatory response and that the measurement of plasma adiponectin levels may be helpful in assessment of CAD risk.